(SOJ[APLMJ UFYVX]Ps - (SNlga(Smrsrynrw Apx}pjws ((SXilrnga(Sw(B,s, 2011)
(SFLVAD]DJ KFOFNL]EFLV AU[FV (B& (SFPPRLFV XJV OJ[APLMJV UFYVX]P UFYVXA VF LVRUURSLA ELAZRULMJ APANYVJ MLPJVJV UFYVXRY VXU]XFV URFV SUADOAXLM]P UFYVX]P URJ LEFAX]P UFYVX]Ps
(SFLVAD]DJ KFOFNL]EFLV AU[FV (B& (SFPPRLFV XJV OJ[APLMJV UFYVX]P UFYVXA VF LVRUURSLA ELAZRULMJ APANYVJ MLPJVJV UFYVXRY VXU]XFV URFV SUADOAXLM]P UFYVX]P URJ LEFAX]P UFYVX]Ps